Optimization of the antioxidant potentials of red pitaya peels and its in vitro skin whitening properties - Vijayakumar, Ramya; Abd Gani, Siti Salwa; Zaidan, Uswatun Hasanah; Halmi, Mohd Izuan Effendi (M D P I AG, 2018)
In this study, response surface methodology (RSM) was employed for the optimization of the antioxidant potentials of red pitaya peels using independent variables: temperature (45–65 °C), ethanol concentration (70–90%, v/v) and time (80–120 min) through its responses, which were DPPH scavenging activity, ferric ion reducing antioxidant power (FRAP), and beta-carotene bleaching (BCB) inhibition, respectively. In Vitro anti-tyrosinase and vitamin C content assays were carried out spectrophotometrically to determine the skin whitening efficacy of the optimized red pitaya peel extract. A gas chromatography-mass spectrometry (GC-MS) analysis was employed to identify the chemical constituents present in the optimized extract. The optimized conditions were ethanol 82% (v/v) for 103 min at 56 °C with values of 75.98% for DPPH, 7.45 mM Fe2+/g dry weight for FRAP and 93.29% for BCB respectively. The in vitro anti-tyrosinase and vitamin C content evaluation of the optimized extract showed a good tyrosinase inhibition of 66.29% with IC50 of 24.06 µg/mL while the vitamin C content was 5.45 mg/g of the extract. The GC-MS analysis revealed the presence of thirty phytoconstituents with l-(+)-ascorbic acid 2,6-dihexadecanoate being the most abundant with a peak area of 14.66%. This study evidently suggests the potential of red pitaya peels to be exploited as a natural skin whitening agent in the cosmeceutical and pharmaceutical formulations.